GUEST EDITORS: ISLAMIC EDUCATION AS THE CORE FOR THE FORMATION OF BARAKAH CAMPUS: Editor Tamu: Pendidikan Islam Nadi Pembentukan Kampus Barakah - Othman, Siti Suriani; Abd Rahman, Mohd Rosmizi Abd; Sabran, Rosidayu; Zainun, Amirah; Othman, Khatijah (‘Abqari Journal, 2019)
This special edition compiles a collection of papers presented at International Conference on Islamic Higher Education (SeIPTI) 2018 organised by Universiti Sains Islam Malaysia (USIM) on 25 to 26 November 2018. SeIPTI is a conference that groups scholars to discuss issues pertaining to Islamic higher education. The fifth conference this year brings about the theme of “Barakah Campus”. Under this theme, various issues have been discussed including the concept of barakah in universities and wider topics that are not confined to merely discussions on Islamic higher education but also broader debates on developments related to Islam in various fields in different kinds of organisations. Hence, this special edition highlights the theme, “Developments in Potential Fields in Achieving Barakah”.